Comparative Study between Endoscopic Aided Septoplasty with Two Handed Technique using Endoholder and Conventional Septoplasty - Pokharel, Apar; Mayya, Naganawalachullu Jaya Prakash; Gautam, Nabin (Journal of College of Medical Sciences-Nepal, 2020)
Introduction: Deviated nasal septum is one of the most common causes for the nasal obstruction. The objective of this study is to compare the surgical outcomes in patients undergoing conventional septoplasty and endoscopic septoplasty in the management of deviated nasal septum. Methods: Prospective comparative study was conducted on 60 patients who presented to the Department of ENT, College of Medical sciences, during a period of one year. The severity of the symptoms was subjectively assessed using NOSE score and objectively assessed using modified Gertner plate. Results: There was significant improvement in functional outcome like NOSE Score and area over the Gertner plate among patients who underwent endoscopic septoplasty. Significant difference in incidence of post-operative nasal synechae and haemorrhage was seen in conventional group compared to endoscopic group. Conclusions: Endoscopic surgery is an evolutionary step towards solving the problems related to deviated nasal septum. It is safe, effective and conservative, alternative to conventional septal surgery.